2021
DOI: 10.1007/s10620-021-07230-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Liver Injury in Patients Hospitalized with COVID-19

Abstract: Introduction The prevalence and significance of acute liver injury in patients with COVID-19 are poorly characterized. Methods Patients with confirmed COVID-19 who were hospitalized in geographically diverse medical centers in North America were included. Demographics, symptoms, laboratory data results, and outcomes were recorded. Linear and logistic regression identified factors associated with liver injury, in-hospital mortality, and length of stay (LOS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 29 publications
2
32
1
Order By: Relevance
“…We also explored the ratio of liver injury during hospitalization, and the results showed that only four Delta and one Omicron variant-infected patients experienced liver injury during hospitalization. Previous studies have shown that liver injury occurs in some COVID-19 patients during hospitalization, but the results vary greatly and significantly higher than our results [24,25]. In this study, only 5 (3.2%) SARS-CoV-2-infected patients experienced in-hospital liver injury, RUCAM scores of two patients supported that liver injury was related to the use of analgesic-antipyretic drugs whereas three patients were considered to be related to SARS-CoV-2 infection.…”
Section: Discussioncontrasting
confidence: 98%
“…We also explored the ratio of liver injury during hospitalization, and the results showed that only four Delta and one Omicron variant-infected patients experienced liver injury during hospitalization. Previous studies have shown that liver injury occurs in some COVID-19 patients during hospitalization, but the results vary greatly and significantly higher than our results [24,25]. In this study, only 5 (3.2%) SARS-CoV-2-infected patients experienced in-hospital liver injury, RUCAM scores of two patients supported that liver injury was related to the use of analgesic-antipyretic drugs whereas three patients were considered to be related to SARS-CoV-2 infection.…”
Section: Discussioncontrasting
confidence: 98%
“…However, at baseline, only 1% and 0.2% of the patients had LI (i.e., AST>200 IU/L) or AST >400 IU/L, respectively. Thus, in accordance with previous studies [ 10 , 14 , 15 ], we confirmed that liver biochemistry abnormalities in COVID-19 patients are usually mild and predominantly hepatocellular, while AST values are more frequently abnormal than ALT. Nevertheless, no indication for liver dysfunction was observed, since no severe abnormalities in INR were recorded (range 0.7-1.3 in patients not receiving anticoagulants).…”
Section: Discussionsupporting
confidence: 93%
“…The pooled prevalence of CLD in hospitalized COVID-19 patients is 3% and similar to uninfected patients [57 ▪▪ ]. The prevalence of advanced fibrosis or cirrhosis in hospitalized COVID-19 patients is 1% [15 ▪ ,16 ▪ ]. Sixty percentage of patients with CLD develop severe COVID-19 [58].…”
Section: Coronavirus Disease 2019 In Patients With Chronic Liver Diseasementioning
confidence: 92%
“…In observational studies of hospitalized patients with COVID-19, aminotransferases were elevated on admission in 20–67%, with 61–83% developing elevated aminotransferases during hospitalization [12,13,14 ▪ –16 ▪ ,17–19]. Aminotransferase elevations are usually less than 3–5 times the upper limit of normal (ULN) [14 ▪ –16 ▪ ]. Elevated serum alkaline phosphatase (ALP) and total bilirubin have been observed in 23–30 and 4–16% of hospitalized patients, respectively [15 ▪ ,16 ▪ ,17].…”
Section: Prevalence and Pattern Of Liver Injury In Coronavirus Diseas...mentioning
confidence: 99%